2011
DOI: 10.1210/jc.2010-1450
|View full text |Cite
|
Sign up to set email alerts
|

Leiomyoma Simultaneously Impair Endometrial BMP-2-Mediated Decidualization and Anticoagulant Expression through Secretion of TGF-β3

Abstract: Leiomyoma-secreted TGF-β3 induces BMP-2 resistance in endometrium by down-regulation of BMPR-2, likely causing defective endometrial decidualization. TGF-β3 also reduces expression of PAI-1, ATIII, and thrombomodulin in endometrium, likely contributing to menorrhagia. A single molecular signal targeting endometrium may mediate both leiomyoma-induced infertility and bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
132
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(142 citation statements)
references
References 43 publications
2
132
0
8
Order By: Relevance
“…Intermenstrual bleeding is more likely related to endometrial instability (30) than to mechanical interference of leiomyomas; therefore, it is possible that women with higher PR expression in the leiomyoma and myometrium also have higher PR signaling in the endometrium and this is the main protective factor against irregular bleeding. Another possible mechanism is via paracrine communication from leiomyoma cells to endometrial stromal cells (31), but this is a complex network involving several growth factors with balanced activity on endometrial thickness and blood coagulation factors, and the net effect of progesterone is unknown. It is interesting that uterine bleeding is reduced by treatment with selective PR modulators through several putative mechanisms such as decreasing uterine blood flow and tumor volume, which may compensate for their progesterone antagonism in the endometrium (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…Intermenstrual bleeding is more likely related to endometrial instability (30) than to mechanical interference of leiomyomas; therefore, it is possible that women with higher PR expression in the leiomyoma and myometrium also have higher PR signaling in the endometrium and this is the main protective factor against irregular bleeding. Another possible mechanism is via paracrine communication from leiomyoma cells to endometrial stromal cells (31), but this is a complex network involving several growth factors with balanced activity on endometrial thickness and blood coagulation factors, and the net effect of progesterone is unknown. It is interesting that uterine bleeding is reduced by treatment with selective PR modulators through several putative mechanisms such as decreasing uterine blood flow and tumor volume, which may compensate for their progesterone antagonism in the endometrium (16,17).…”
Section: Discussionmentioning
confidence: 99%
“…This global effect of the myoma on endometrium suggests the presence of a diffusible factor that would influence endometrial receptivity remote from the myoma itself. Indeed, we have recently reported that TGFb secreted by myomas leads to decreased BMP receptor expression and subsequent HOXA10 repression (Sinclair et al 2011). Leiomyoma alter endometrial receptivity by secreting TGFb and altering genes including HOXA10 that are required for implantation.…”
Section: Hox Genes and Leiomyomamentioning
confidence: 97%
“…HOXA10 is expressed in human myometrium and its expression also has a menstrual cycledependent pattern. In vitro, HOXA10 expression is induced in endometrial stromal cells by progesterone, but in the primary myometrial cells, progesterone suppresses HOXA10 expression (Cermik et al 2001;Matsuzaki et al 2009;Rackow and Taylor 2010;Sinclair et al 2011). It is clear that there are different factors involved in the regulation of HOXA10 by progesterone in myometrium than endometrium.…”
Section: Hox Genes and Leiomyomamentioning
confidence: 99%
“…It has been demonstrated that progesterone (alone or in combination with 17β-estradiol) enhances the expression of CS/HSPG serglycin and DS/CSPG biglycan and versican in endometrial endothelial cells (8). Another potential regulator of endometrial PG synthesis is TGF-β3, which is capable of suppressing HSPG expression in endometrial stromal fibroblasts (9).…”
Section: Pgs In Human Endometriummentioning
confidence: 99%